Association of Serum Calcium and Vitamin D with Benign Paroxysmal Positional Vertigo - Ron Jacob Thomas (Thieme Revinter Publicações Ltda., 2021)
Introduction Benign paroxysmal positional vertigo (BPPV) is one of the common disorders of the peripheral vestibular system. The prevalence of BPPV is found to be higher among middle-aged women. Objectives To estimate the serum levels of calcium and vitamin D in patients with BPPV, and to study their association. Methods The present is a hospital-based prospective case-control study. Venous blood samples of the 49 patients with BPPV and an equal number of age- and gender-matched individuals were recruited and submitted to an analysis of the serum levels of calcium and vitamin D. Results Among the cases, 67.3% were found to be females, and 32.7% were males. Most of the 30 cases (61.3%) were aged > 40 years. The mean age of the cases was 44.39 years. The mean serum level of vitamin D in the cases was of 21.26 ng/ml compared with 17.59 ng/ml in the controls. The mean serum level of calcium was of 9.33 mg/dl in the cases, compared with 8.95 mg/dl in the controls. There was no significant difference in the serum levels of vitamin D and calcium between cases and controls. Conclusion We could not establish any correlation between the serum levels of calcium and vitamin D with BPPV. However, a negative relationship was found between the serum levels of vitamin D and the number of episodes of BPPV (p = 0.012).